Genetic Variability and Marker Trait Association analysis of Various Phenological and Yield Related Traits for Heat Tolerance in Chickpea (Cicer arietinum L.) - Jha, Uday Chand; Kole, Paresh Chandra; Singh, Narendra Pratap (International Journal of Bio-resource and Stress Management, 2018)
Increasing incidence of heat stress (HS) is receiving serious attention as it causes significant yield reduction in various crops including chickpea worldwide. Here, we investigated the existing genetic variability for various yield related crucial traits for developing heat tolerant genotype under field condition in a panel of seventy eight chickpea genotypes under normal and HS condition via conducting augmented design analysis. Analysis of variance (ANOVA) exhibited significance difference among the checks for first flowering (FF), days to 50% flowering (50F), days to pod initiation (DPI), days to maturity (MAT), plant height (PH), empty pod (EP), yield plant-1 (YPP), biological yield (BioY), harvest index (HI%), and 100 seed weight (100 SW) under normal condition. While, under HS condition significance difference among the checks for the following traits FF, 50F, PH, EP, YPP and 100SW were recorded. Additionally, to seek marker trait association (MTA), we examined MTAs for the given phenological and yield related traits under both normal and late sown condition via employing 81 simple sequence repeat (SSR) markers in the given set of genotypes. A total of 37 significant MTAs (under normal condition) and 38 significant MTAs (under HS condition) were obtained for various phenological and yield related traits. Additionally, eighteen MTAs for heat tolerance index (HTI), stress susceptibility index (SSI), yield index (YI), mean productivity (MP) and geometric mean productivity (GMP) were recorded.